PENGARUH MODEL SELF ORGANIZED LEARNING ENVIRONMENT (SOLE) TERHADAP KEMAMPUAN MENULIS TEKS TANGGAPAN SISWA KELAS VII SMP NEGERI 37 MEDAN TAHUN PEMBELAJARAN 2024/2025 - Candy Carobelli Sitompul; Trisnawati Hutagalung (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Students’ ability to write response texts still faces challenges, particularly in terms of structure and linguistic features. This study aims to examine the effect of the Self Organized Learning Environment (SOLE) model on the writing ability of seventh-grade students at SMP Negeri 37 Medan. The research employed an experimental method with a two group post-test design. The sample consisted of 62 students selected through random sampling, divided into an experimental class (32 students) and a control class (32 students). Data were collected through observation, tests, and documentation, and analyzed using prerequisite tests (normality and homogeneity) as well as hypothesis testing. The results indicated that the data were normally distributed and homogeneous, and that the SOLE model had a significant effect on writing ability, as evidenced by thitung > ttabel(9.77 > 1.90). The average score of the experimental class was 83.15 (capable category), higher than that of the control class, which was 64.59 (fair category). These findings suggest that the SOLE model is effective in improving students’ response text writing skills, and it is recommended that Indonesian language teachers apply this model as an alternative instructional strategy.